Eliza Jane Trimble Thompson report - Thompson, Eliza Jane Trimble, 1816-1905.
Report on the activities of the Woman's Christian Temperance Union in relation to the temperance movement from 1873 to 1874.
Temperance crusader.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Woman's Christian Temperance Union; Temperance -- United States -- Societies, etc; Women social reformers -- United States; Reformers